2019
DOI: 10.1021/acsomega.9b00535
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Synthesis of Non-Natural Monoterpene O-Glycosides Exhibiting Superior Antibacterial and Antinematodal Properties

Abstract: A promiscuous Bacillus glycosyltransferase (YjiC) was explored for the enzymatic synthesis of monoterpene O -glycosides in vitro and in vivo. YjiC converted seven monoterpenes into 41 different sugar-conjugated novel glycoside derivatives. The whole-cell biotransformation of the same set of monoterpenes exhibited robust enzyme activity to synthesize O -glucosyl derivatives from Escherichia coli . These newly synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
1
12
0
2
Order By: Relevance
“…Luteolin-rich herbal extracts have been used for a long time as traditional herbal remedies [ 18 , 19 ]. We observed that luteolin had mild bactericidal activity in vitro ( S1 Fig ), as reported [ 20 ]. Moreover, we also found that luteolin treatment significantly activated macrophages, as evidenced by increased expression of co-stimulatory molecules and improved bactericidal activity ( S2A & S2B Fig ).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Luteolin-rich herbal extracts have been used for a long time as traditional herbal remedies [ 18 , 19 ]. We observed that luteolin had mild bactericidal activity in vitro ( S1 Fig ), as reported [ 20 ]. Moreover, we also found that luteolin treatment significantly activated macrophages, as evidenced by increased expression of co-stimulatory molecules and improved bactericidal activity ( S2A & S2B Fig ).…”
Section: Introductionsupporting
confidence: 89%
“…Taken together, these findings suggested that luteolin might have potent immunomodulatory effects, which along with selective enrichment of the T CM pool may be highly beneficial in combating TB. Therefore, we performed a proof of concept study to explore the effects of luteolin on the memory T cell responses after BCG immunization, using the intraperitoneal route of administration to maintain homogeneity in dosage and to achieve higher bioavailability than the oral route [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, this effect did not appear to be synergistic with isoniazid ( S1 Fig ). We then treated mice with Luteolin at 5 mg/kg body weight using the intraperitoneal route of administration to maintain homogeneity in dosage and to achieve higher bioavailability than the oral route [ 29 , 39 ], starting at 15 days after infection with an aerosol dose (~220 CFU/mouse) of M . tb .…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated whether Luteolin, either alone or in combination with existing antibiotics, exerts beneficial effects against primary M.tb infection. Luteolin did not exerted any bactericidal effects on M.tb in vitro in a cell free system at up to 75 μM/mL, but a significant reduction in growth was seen at a higher concentration of 100 μM/mL (S1 Fig) . However, this effect did not appear to be synergistic with isoniazid (S1 Fig) . We then treated mice with Luteolin at 5 mg/kg body weight using the intraperitoneal route of administration to maintain homogeneity in dosage and to achieve higher bioavailability than the oral route [29,39] Next, we performed histological analyses of the lungs. Mice treated with Luteolin or with Luteolin+INH showed increased numbers of infiltrating cells and reduced levels of necrosis compared with controls (Fig 1F).…”
Section: Luteolin Treatment Reduces the Bacterial Burden In Mtb Infected Micementioning
confidence: 99%
“…GTs from various organisms have been used to glucosylate diverse sets of plant natural products, specifically flavonoids [10,11].In this study, we have investigated the application of a GT, YjiC from non-pathogenic Bacillus licheniformis DSM 13 strain for glycosylation of various industrially important amino (NH 2 ) and thiol (SH) functional groupcontaining acceptor substrates. YjiC has been extensively studied for its donor and acceptor substrate promiscuity towards nucleophilic O-glycosylation of diverse sets of natural products using NDP-D/L-sugars as donor substrates [12,13]. Nucleophilic N-, S-, C-glycosylation is regarded as rare in comparison to O-glycosylation of natural products.…”
mentioning
confidence: 99%